2-Arachidonoylglycerol impairs human cytotrophoblast cells syncytialization: Influence of endocannabinoid signalling in placental development. (5th January 2015) - Costa, M.A.; Keating, E.; Fonseca, B.M.; Teixeira, N.A.; Correia-da-Silva, G.
Highlights: Cytotrophoblasts and syncytiotrophoblast express 2-AG main metabolic enzymes. 2-AG impairs functional and morphological differentiation of human cytotrophoblasts. 2-AG effects are mediated by the activation of cannabinoid receptors. 2-AG effects may result from the inhibition of cAMP/PKA signalling pathway. Abstract: A balanced cytotrophoblast cell turnover is crucial for placental development and anomalies in this process associated with gestational diseases. The endocannabinoid system (ECS) has emerged as a new player in several biological processes. However, its influence during placental development is still unknown. We report here the expression of the endocannabinoid 2-arachidonoylglycerol (2-AG) main metabolic enzymes in human cytotrophoblasts and syncytiotrophoblast. We also showed that 2-AG induced a decrease in placental alkaline phosphatase activity, human chorionic gonadotropin secretion and Leptin mRNA levels. Moreover, 2-AG reduced glial cell missing 1 and syncytin-2 transcription and the number of nuclei in syncytium. These effects were mediated by cannabinoid receptors and may result from 2-AG inhibition of the cAMP/PKA signalling pathway. Our data suggest that 2-AG may interfere with the biochemical and morphological differentiation of human cytotrophoblasts, through a CB receptor-dependent mechanism, shedding light on a role for the ECS in placental development.